The in vivo T helper type 17 and regulatory T cell immune responses to Aggregatibacter actinomycetemcomitans. (27th June 2017) - Mahabady, S.; Tjokro, N.; Aharonian, S.; Zadeh, H.H.; Chen, C.; Allayee, H.; Sedghizadeh, P.P.
Summary: The periodontal pathogen Aggregatibacter actinomycetemcomitans is known to elicit a systemic immune response in the infected host, and occasionally causes non‐oral infections. Detailed information on its immunopathological responses and the involvement of bacterial virulence factors remains to be elucidated. The aim of this study was to assess the systemic immune response to A. actinomycetemcomitans oral infection. We used an animal model that simulates systemic dissemination of the bacteria by injecting live wild‐type (WT) D7S‐1 and a double knockout mutant of leukotoxin and cytolethal distending toxin (Δ ltx Δ cdt ) A. actinomycetemcomitans strains in rat oral mucosa. Draining lymph nodes were examined for regulatory T (Treg) and T helper type 17 (Th17) cell subsets and their associated mediators. An increase in the proportion of Th17 cells and a decrease in Treg cells over the experimental period of 3 weeks were similarly observed for rats challenged with WT and Δ ltx Δ cdt . Significant upregulation and downregulation of proinflammatory cytokines in the Th17 gene pathway was noted, as well as several qualitative differences between WT and Δ ltx Δ cdt . Furthermore, we observed differential fold regulation in key genes associated with a proinflammatory response in ΔltxΔcdt‐ inoculated rats relative to D7S‐1 group. This suggests that although the knockout of these two virulence factors ( ΔltxΔcdt ) may suppress certain proinflammatory genes, it causes similar over‐expression of other genes compared with D7S‐1, indicating a common factor that still remains in the pathogenicity of A. actinomycetemcomitans .